Self-control and Reactive Aggression in Mexican Adolescents (European Journal of Child Development, Education and Psychopathology, 2021)
Reactive and proactive aggression are two of the main types of aggression identified in bullying. Some research suggests that self-control contributes to a decrease in proactive and reactive aggression. However, studies that have investigated the relationships of these variables with self-control in the Mexican context are scarce. The aim of this study was to explore the relationships between self-control with reactive and proactive aggression in Mexican adolescents. The sample was selected in a non-probabilistic way, the participants in this study were 300 adolescents with ages between 12 and 18 (M age = 14, SD = 1.55), 147 (49 %) were male, while 153 (51 %) were female. Self-control was measured with the subscale Values in Action Inventory of Strengths (VIA-Youth; Park & Peterson, 2006), for reactive and proactive aggression we use the Reactive and Proactive Aggression Questionnaire (QRP; Raine et al., 2006). Results indicate that self-control was negatively and significantly related to reactive and proactive aggression. This may indicate that adolescents with a higher level of self-control have a lower frequency of proactive aggression. this study contributes to understand the different types of aggression in school bullying in adolescents. In addition, the results suggest that self-control may decrease peer aggression.
Keywords: Self-control; reactive aggression; proactive aggression; adolescents